In-situ EBSD study on the cube texture evolution in 3 wt% Si steel complemented by ex-situ EBSD experiment — From nucleation to grain growth. (March 2019) - Takajo, S.; Merriman, C.C.; Vogel, S.C.; Field, D.P.
Abstract: Cube ( { 100 } 〈 001 〉 ) texture in steel sheet is preferable for magnetic applications since the easy magnetization axis 〈 001 〉 is parallel to the rolling and transverse directions which are common magnetic flux directions. Several advanced processes have been proposed to obtain the cube texture, such as severe cold rolling or vacuum annealing all requiring unconventional processing techniques. Here, we report a much simpler processing route leading to a strong cube texture in 3 wt% Si steel, which is based on conventional processing techniques. The cube orientation is developed by means of increasing the grain size before cold rolling. In this manuscript, the mechanism of the creation of the cube oriented grain is described with regards to nucleation and grain growth. Knowledge of the nucleation site of the cube oriented grains, determined by conventional ex-situ electron back-scatter diffraction (EBSD), allowed to define the observation area for in-situ heating EBSD measurements to observe where cube oriented grains were formed. The following sequence of cube texture evolution is proposed: (i) grains with cube and near cube orientations are nucleated from fragments of deformed { 411 } 〈 148 〉 grains; (ii) these grains grow inside prior grain boundaries and their coarsening speed is higher than that of other grains with different orientations due to a higher relative grain boundary mobility; (iii) the cube oriented grains start to grow beyond the prior grain boundaries and become dominant due to the size effect. Nuclei for cube orientations were experimentally observed and an equation is derived to predict the relative grain bounday mobility as a function of misorientation angle and temperature. Graphical abstract: Image 1